Mathematical Engagement In Interactive Learning: A Case Study Of The Use Of Lumio In Understanding The Concept Of Normal Distribution - Lestari, Indri; Hadi, Windia; Giyanti, Giyanti; Khotimah, Khotimah (Koordinat Jurnal MIPA, 2025)
Understanding the concept of normal distribution in statistics is often challenging for students, as it requires a deep understanding of symmetry, probability distribution, and the use of normal distribution tables. These challenges are often caused by difficulties in connecting theoretical concepts with data visualization and in comprehending z-score transformations. This study aims to analyze students' mathematical engagement in understanding the concept of normal distribution using Lumio-based interactive media. The study employed a quantitative, quasi-experimental design, with a pre-test post-test control group design. The experimental group engaged in learning using Lumio-based interactive media, while the control group received traditional lecture-based teaching methods. The research instruments included a concept comprehension test, a mathematical engagement questionnaire, and an analysis of Lumio activity logs. The data were analyzed using paired sample t-tests and ANCOVA to evaluate the effectiveness of Lumio in improving students' mathematical engagement and conceptual understanding. The results showed a significant difference between pre-test and post-test scores in both the experimental and control groups. The experimental group, which used Lumio, showed a significantly higher improvement in both conceptual understanding and engagement compared to the control group. The findings suggest that using Lumio-based learning significantly enhanced students' engagement and understanding of normal distribution, compared to the conventional teaching methods